Understanding Networks: The functions of research policy networks - Mendizabal, Enrique (ODI, 2006)
We are constantly talking about networks. Banks use their networks to offer global services to customers; airlines fly passengers all over t he world via their networks of partners; news agencies use media netwo rks to keep us informed every minute of the day; and terrorist network s threaten citizens around the world. The importance of networks exten ds to the development sector: they organise civil society to advocate for and implement change; they link the local with the global, the pri vate with the public; and they provide spaces for the creation, sharin g and dissemination of knowledge. In a way, networks seem to make anyt hing and everything happen. But we have yet to understand what they ar e and what they can and cannot do. In the development literature, a hu ge variety of policy and social network concepts and applications exis ts. This paper attempts to set out a framework to help clarify what re search policy networks do.